GENITAL AND PERIGENITAL HUMAN PAPILOMAVIRUS (HPV) INFECTION IN SMALL CHILD - Carmen Sălăvăstru; T. Cristodulo; M. Panduru; A. Colțoiu; G.S. Țiplica (Amaltea Medical Publishing House, 2009)
Genital and perigenital human papilomavirus (HPV) infection in children has an incidence of 1.8% and the most frequently identified viral types are HPV 6 and 11. The mechanism of transmission of HPV to the anogenital area in children is vertical or perinatal transmission from an HPV-infected maternal genital tract (most likely in children under three years of age), horizontal transmission by auto- or heteroinoculation from cutaneous or mucosal warts elsewhere, and transmission by sexual abuse. The authors present several cases of infants aged under 24 month old referred to the clinic for multiple papillary lesions mainly found in anogenital region, the external genitalia and contiguous mucous membranes which, due to chronic friction, result in papules that are less verrucous and vary in color from pink to brown. Neither patient presented sings of sexual abuse; VDRL, TPHA and anti-HIV Ab were negative in all cases. The therapeutic approach was very difficult because of the extensive affected area and the patients' age. Initially, we used several applications of trichloracetic acid and electrodessication with very good results and a free of lesion mean period of two month. In one case the lesions reappeared and we combined several therapeutic modalities: podophyllin, electrodessication, cauterization, with good results. As a conclusion, treating extensive affected areas of HPV infection in children may be challenging and the need of repeated applications might be followed by side effects.